International Classification of Functioning, Disability, and Health in women with breast cancer: a proposal for measurement instruments - Flávia Nascimento de Carvalho; Rosalina Jorge Koifman; Anke Bergmann (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
The International Classification of Functioning, Disability, and Health (ICF) aims at standardization, but its applicability requires consistent instruments. In Brazil, invasive therapeutic approaches are frequent, leading to functional alterations. The current study thus aimed to identify and discuss instruments capable of measuring ICF core set codes for breast cancer. The review included ICF studies in women with breast cancer diagnosis and studies with the objective of translating and validating instruments for the Brazilian population, and consistent with the codes. Review studies, systematic or not, were excluded. Eight instruments were selected, and the WHOQOL-Bref was the most comprehensive. The use of various instruments showed 19 coinciding codes, and the instruments as a whole covered 58 of the total of 81 codes. The use of multiple instruments is time-consuming, so new studies are needed to propose parsimonious tools capable of measuring functioning in women treated for breast cancer.